KOMITMEN DAN TANGGUNG JAWAB DALAM PERNIKAHAN: PERSPEKTIF PENDIDIKAN KRISTEN - Purba, Asmat; -, Yonce (Jurnal TEDC; Vol 19 No 3 (2025): JURNAL TEDC, 2025)
This article is a literature study that outlines how commitment and responsibility in marriage are viewed from a Christian education perspective. It poses a challenge for contemporary Christian educators to prepare strong Christian marriages amid the increasing prevalence of divorce in recent times. To explain this, the author presents information from primary and secondary sources on the topic, which is then described descriptively. The study highlights the need to prepare Christian educators so that they can guide Generation Z to enter marriage as strong couples capable of facing the challenges of the times. Christian educators are able to recognize challenges and opportunities to restore damaged families, helping couples become genuine partners who honor the covenant of marriage according to God's word: what God has united, man must not separate (Matthew 19:6). Method The research used is a descriptive method, with a qualitative literature study (library research) approach results of this study indicate that families, Christian schools, and churches must prepare several important programs for preparing young people who will later become husband and wife.